2003
DOI: 10.1053/ejvs.2002.1925
|View full text |Cite
|
Sign up to set email alerts
|

Seizures after carotid endarterectomy: Hyperperfusion, dysautoregulation or hypertensive encephalopathy?

Abstract: Post-CEA seizure was associated with adverse outcome. Most were labile hypertensives with severe bilateral carotid/vertebral disease. MCAV changes suggested poor collateral recruitment, but no consistent pattern of early hyperperfusion emerged. It remains uncertain whether high MCAVs and severe hypertension after seizure onset are cause or effect. Clinicians treating these patients in acute medical units were generally unaware of the "post-CEA hyperperfusion syndrome" and tended to treat the hypertension less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 13 publications
(22 reference statements)
2
42
0
5
Order By: Relevance
“…Seizures or epilepsy are one of the major symptoms in patients with hyperperfusion syndrome, 17,22) but surprisingly few reports describe the EEG findings. EEG obtained during hyperperfusion syndrome revealed periodic lateralizing epileptiform discharges (PLEDs) on the side of the brain ipsilateral to the CEA, even in the absence of seizures or during the postictal state.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures or epilepsy are one of the major symptoms in patients with hyperperfusion syndrome, 17,22) but surprisingly few reports describe the EEG findings. EEG obtained during hyperperfusion syndrome revealed periodic lateralizing epileptiform discharges (PLEDs) on the side of the brain ipsilateral to the CEA, even in the absence of seizures or during the postictal state.…”
Section: Discussionmentioning
confidence: 99%
“…23,33) Surprisingly few previous reports described EEG findings, 10,15,31) although seizures or epilepsy are one of the major symptoms in patients with CHS after CEA or CAS. 13,23,25,31) Only EEG examinations of 10 patients with CHS for several days after CEA revealed periodic lateralizing epileptiform discharges on the operated hemisphere, even in the absence of seizures or during the postictal state. 28) Since periodic lateralizing epileptiform discharges are one of the EEG patterns in patients with NCSE, 2,12,22) these cases probably had similar pathophysiological conditions to those of Case 3 in the development of CHS.…”
Section: Eeg Of Hyperperfusion Syndromementioning
confidence: 99%
“…SPECT is sensitive for recognizing CHS, differentiating between ischemia and hyperperfusion, and identifying patients at risk for hyperperfusion after CEA (Hosoda et al, 2001;Naylor et al, 2003;Sfyroeras et al, 2006). Several studies using SPECT have demonstrated that decreased CVR using acetazolamide is a significant predictor of post-CEA hyperperfusion Yoshimoto et al, 1997).…”
Section: Diagnosing Hemodynamic Reservementioning
confidence: 99%
“…Curiously, this study was unable to demonstrate a relation between CHS and factors like postprocedural hypertension, advanced age, degree of ipsilateral stenosis, or contralateral disease. Regarding prior stroke as a risk factor for CHS, many authors have found that diseases like diabetes mellitus or longstanding pre-existing hypertension in which microangiopathy affects the endothelium of small vessels predispose to hyperperfusion and CHS (Chamorro et al, 2000;McCabe et al, 1999;Naylor et al, 2003;van Mook et al, 2005). Tietke et al (2010) analyzed the outcomes of 358 patients treated with CAS using small closed-cell stents without distal protection.…”
Section: Extracranial Carotid Angioplastymentioning
confidence: 99%